2013
DOI: 10.21121/eab.2013219490
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rates and Exchange Rate Relationship in BRIC-T Countries

Abstract: The BRIC is a grouping acronym that refers to the countries of Brazil, Russia, India and China, which are deemed to be at a similar stage of economic development. According to the report of Goldman and Sachs (2009), it is expected that the BRIC countries will be as big as the G7 by 2032. Not only the population and land area features of the BRIC countries, but also the speed of the growth rate and increasing proportion in the international trade have made them significant actors in the global economy. Turkey h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 64 publications
4
11
0
1
Order By: Relevance
“…On the other hand, the results indicate one-way causality from M_DL_USDTRY towards M_DL_BOND2 for holding periods of 6.6-7.4 and 3.6-4.2 months, and bidirectional causality at the frequencies higher than ( ≥) 1.94, that is, shorter than 3.23 months. These findings reinforce the conclusion drawn by Gün et al (2016) and Şentürk and Dücan (2014) with BOND⇒USDTRY in Turkey; by Kayhan et al (2013) with REER⇒BOND in the short-run in Brazil and India; with REER⇒BOND in the medium-run and BOND⇒REER in the long-run in China; by Ozer and Kamisli (2016) with BOND⇒EURTRY in the short-run and with EURTRY⇒BOND in the long-run in Turkey; by Hacker et al (2014) who find bidirectional causality between the interest rate differential and Swedish Krona against USD, EUR, JPY, GBP, NOK, CHF, and KRW at the medium and higher wavelet scales; and by Özpınar et al (2018) with USDTRY⇔BOND in Turkey.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the results indicate one-way causality from M_DL_USDTRY towards M_DL_BOND2 for holding periods of 6.6-7.4 and 3.6-4.2 months, and bidirectional causality at the frequencies higher than ( ≥) 1.94, that is, shorter than 3.23 months. These findings reinforce the conclusion drawn by Gün et al (2016) and Şentürk and Dücan (2014) with BOND⇒USDTRY in Turkey; by Kayhan et al (2013) with REER⇒BOND in the short-run in Brazil and India; with REER⇒BOND in the medium-run and BOND⇒REER in the long-run in China; by Ozer and Kamisli (2016) with BOND⇒EURTRY in the short-run and with EURTRY⇒BOND in the long-run in Turkey; by Hacker et al (2014) who find bidirectional causality between the interest rate differential and Swedish Krona against USD, EUR, JPY, GBP, NOK, CHF, and KRW at the medium and higher wavelet scales; and by Özpınar et al (2018) with USDTRY⇔BOND in Turkey.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…By building an MS-VAR model with regime change and asymmetric frequency domain and rolling windows causality analysis, the authors found that CDS spreads are partially forcing variables for Euro and Lira. A similar econometric approach is used by Kayhan et al (2013) to find the relation between the exchange rate and interest rate for Turkey. A non-linear and frequency domain causality test was employed to find the relation between BRIC countries and Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 (June 2021) 109-138 market. This result corroborates the mostly negative DCC-GARCH correlation between the return series, but contradicts the findings of Kayhan, Bayat, and Ugur (2013) that exchange rate shocks induce positive changes in interest rate in BRIC-T countries, which is in tandem with the Monetarists' view that contractionary monetary policy through increase in interest rate leads to exchange rate appreciation, thus moderation in exchange rate volatility. However, the estimated parameter, β 21 which measures the volatility spillover from money market to foreign exchange market is positive but not statistically significant, which supports the results of the estimated DCC-GARCH that show very few periods of low positive correlation.…”
Section: -138supporting
confidence: 41%
“…The extant empirical findings are mixed. For instance, Kayhan, Bayat, and Ugur (2013), Shodipe (2018), Capasso, et al (2019, Nnamani and Anyanwaokoro (2019) and Adeshola et al (2020) find positive impact of interest rate on exchange rate, while Babatunde and Olufemi (2014) and Kisaka and Ouma (2017) established negative relationship.…”
Section: -138mentioning
confidence: 98%
“…Some studies report bidirectional causality between interest and exchange rates. Such studies include Hacker, Karlsson and Månsson (2014), Paramati andGupta (2011), Srinivasan, Kalaivani andDevakumar (2014) and Kayhan, Bayat and Uğur (2013).…”
Section: Literature Review and Economic Theorymentioning
confidence: 99%